2001
DOI: 10.1017/s0952836901000139
|View full text |Cite
|
Sign up to set email alerts
|

The reproductive strategy of giant pandas (Ailuropoda melanoleuca): infant growth and development and mother–infant relationships

Abstract: Reproductive activities of six giant panda females (Ailuropoda melanoleuca) living in the Qinling Mountains of China (Shaanxi Province) were recorded from 1989 into early 1995. Data on mating and birth dates, litter size, cub sex and den use were collected for three of the pandas. At this site, pregnant females migrated to lower elevations in advance of other pandas to seek dens for birthing. One dam was videotaped in the den with her cub from birth to the end of the denning phase at 94 days of age. This cub w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
96
2
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 97 publications
(105 citation statements)
references
References 35 publications
6
96
2
1
Order By: Relevance
“…These findings correspond with analysis of studbook data [4]. This is different than the other bear species of the Northern hemisphere (American and Asiatic black bear, brown bear, polar bear, sloth bear and giant panda), which mate from spring to summer and birth mostly in early winter [1,2,[9][10][11][12][13][14][15][16][17]. In the other tropical bear species, the spectacled bear, cubs are born between December and February, a couple of months before fruit production is at its highest, so that the cubs can feed on fruits [18,19].…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…These findings correspond with analysis of studbook data [4]. This is different than the other bear species of the Northern hemisphere (American and Asiatic black bear, brown bear, polar bear, sloth bear and giant panda), which mate from spring to summer and birth mostly in early winter [1,2,[9][10][11][12][13][14][15][16][17]. In the other tropical bear species, the spectacled bear, cubs are born between December and February, a couple of months before fruit production is at its highest, so that the cubs can feed on fruits [18,19].…”
Section: Discussionsupporting
confidence: 76%
“…Most likely this variable length is due to different length of the embryonic diapause (delayed implantation), which is confirmed to occur in American and Asiatic black bears, brown bears, spectacled bears and polar bears, with implantation of the blastocyst occurring in November. Progesterone concentrations during diapause are low, and increase only gradually until implantation, which is characterized by a sharp increase and high progesterone levels until parturition [1,2,[10][11][12][13][14][15][16][17][18][32][33][34]. Progesterone metabolites in the pregnant animal 'Bali' increased above threshold levels approximately one month after mating and decreased 2 weeks before parturition.…”
Section: Discussionmentioning
confidence: 99%
“…But the ratio between mean peak progesterone to total gestation length is similar in the two species (60/225 daysZ0.27 in brown bears and 29/124 daysZ0.24 in pandas). Delayed implantation is believed to be an example of phylogenetic conservatism (Zhu et al 2001), or a trait the panda has inherited long ago as a result of its ursid ancestry. The similarity in this ratio provides some degree of support for this theory.…”
Section: Characterizing Delayed Implantation In Giant Pandasmentioning
confidence: 99%
“…While there has been extensive research on the detection of estrus and mating of giant pandas in captivity , McGeehan et al 2002, Zhang et al 2004) in addition to infant care and development (Zhang et al 1996, Zhu et al 2001, little has been reported on the crucial stage between these two -development of the giant panda fetus and changes in the pregnant mother's physiology. The reason for this is perhaps that pregnancy has been notoriously difficult to detect in giant pandas in part because they gain little weight and their fetuses develop late (Sutherland-Smith et al 2004).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation